Rasch Model Analysis of the Qana’ah Measurement Instrument among Early Adulthood - Noviyanti Fitri; M. Nursalim Malay; Nurul Isnaini (Psikoislamedia: Jurnal Psikologi, 2026)
Early adults in Indonesia currently face complex psychological challenges, including career pressures, materialistic social comparisons that trigger life dissatisfaction, anxiety, declining psychological well-being, and increased risk of depression. In addition, the lack of standardized qana’ah measurement instruments with strong psychometric properties remains a major challenge in Islamic psychology research. This study aimed to develop a qana’ah measurement instrument for early adults using a modern psychometric approach based on the Rasch Model. Employing a quantitative non-experimental design and modern psychometric analysis via the Rasch Model with Winsteps version 3.73 software, the study involved 503 early adult participants aged 18–40 years. The results showed that out of 45 initial items, 38 items met the Rasch Model fit criteria. High content validity was evidenced by an Aiken’s V value of 0.913. The instrument demonstrated excellent reliability, with Cronbach’s alpha and McDonald’s omega both at 0.96, person reliability of 0.90, and item reliability of 0.98. Consequently, the developed qana’ah instrument is declared valid and reliable for measuring qana’ah levels among early adults.